Ekspresi COX-2 setelah pemberian ekstrak etanolik kulit manggis (Garcinia mangostana Linn) pada tikus wistar (COX-2 expression after mangosteen rind (Garcinia mangostana Linn) etanolic extract administration in wistar rats) - Rendra Chriestedy Prasetya; Tetiana Haniastuti; Nunuk Purwanti (Dental Journal (Majalah Kedokteran Gigi), 2013)
Background: Cyclooxygenase is an enzyme for prostaglandins (PGs) synthesis from arachidonic acid. Cyclooxygenase have been characterized and named as COX-1 and COX-2. COX-1 is responsible for constitutive PGs production under physiological condition and maintains normal function. On the other hand, while COX-2 expression is inducible by cytokines and endotoxin. Periodontitis is a chronic inflammatory disease caused by anaerobic bacteria especially gram negative bacteria. The periodontitis occurrence is followed by increased of COX-2 expression. Mangosteen rind (Garcinia mangostana Linn) contains gamma mangostin which inhibits the synthesis of PGE2 through inhibition of COX-2 expression. Purpose: This research was aimed to study COX-2 expression in experimental-induced periodontitis in wistar rats after mangosteen rind etanolic extract administration. Methods: Forty eight male wistar rats were induced periodontitis by putting silk ligature subgingivally around the cervical of the anterior lower teeth for 7 days. After the ligation was taken out, the rats were divided into 4 groups, and treated orally with mangosteen rind extract 60 mg/kg BB, 30 mg/kg BB, ibuprofen and saline respectively. The rats were sacrificed on the 1st, 3rd, 4th, 7th day after the treatment. The rats’ anterior lower jaws were processed for paraffin embedded tissue, cut serially and stained with immunohistochemistry. COX-2 expression were observed and counted under the microscope (400x). The data were analyzed using kruskall wallis test. Results: Kruskal wallis test showed a significant difference COX-2 expression among group indicating that mangosteen rind etanolic extract affected COX-2 expression. Conclusion: Mangosteen rind etanolic extract reduced COX-2 expression in periodontitis rats.Latar belakang: Siklooksigenase adalah enzim yang mensintesis prostaglandin (PG) dari asam arakhidonat. Siklooksigenase dibagi menjadi 2 yaitu COX-1 dan COX-2. COX-1 bertanggung jawab pada sintesis PG dalam kondisi fisiologis dan mempertahankan fungsi normal, sedangkan ekspresi COX-2 dapat terinduksi oleh sitokin dan endotoksin. Periodontitis adalah penyakit peradangan kronis yang disebabkan oleh bakteri anaerob terutama bakteri gram negatif. Terjadinya periodontitis diikuti oleh peningkatan ekspresi COX-2. Kulit buah manggis (Garcinia mangostana Linn) mengandung mangostin gamma yang menghambat sintesis PGE2 melalui penghambatan COX-2. Tujuan: Penelitian ini bertujuan untuk meneliti ekspresi COX-2 pada tikus wistar jantan yang diinduksi periodontitis setelah pemberian ekstrak etanolik kulit manggis. Metode: Empat puluh delapan ekor tikus wistar jantan diinduksi periodontitis dengan meletakkan ligatur sutra pada subgingiva sevikal gigi anterior rahang bawah selama 7 hari. Setelah ligatur dilepas, tikus dibagi dalam 4 kelompok yaitu ekstrak kulit manggis dosis 60 mg/kg BB, 30 mg/kg BB, ibuprofen dan saline dengan pemberian secara peroral. Tikus didekapitasi pada hari ke-1,3, 5 dan 7 setelah perlakuan. Rahang bawah gigi depan dilakukan pemrosesan menjadi blok paraffin, dipotong serial dan dilakukan pewarnaan imunohistokimia. Ekspresi COX-2 diamati di bawah mikroskop dengan perbesaran 400x. Data pengamatan dianalisa dengan uji kruskall wallis. Hasil: Uji kruskall wallis menunjukkan terdapat perbedaan bermakna ekspresi COX-2 diantara kelompok perlakuan yang mengindikasikan bahwa ekstrak kulit manggis mempengaruhi ekspresi COX-2. Simpulan: Ektrak etanolik kulit manggis menurunkan ekspresi COX-2 pada tikus dengan periodontitis.